Combined imaging of potassium and sodium in human skeletal muscle tissue at 7 T. Issue 1 (31st August 2020) - Gast, Lena V.; Völker, Stefanie; Utzschneider, Matthias; Linz, Peter; Wilferth, Tobias; Müller, Max; Kopp, Christoph; Hensel, Bernhard; Uder, Michael; Nagel, Armin M.
Abstract : Purpose: To validate the feasibility of quantitative combined potassium ( 39 K) and sodium ( 23 Na) MRI in human calf muscle tissue, as well as to evaluate the reproducibility of the apparent tissue potassium concentration (aTPC) and apparent tissue sodium concentration (aTSC) determination in healthy muscle tissue. Methods: Quantitative 23 Na and 39 K MRI acquisition protocols were implemented on a 7 T MR system. A double‐resonant 23 Na/ 39 K birdcage RF coil was used. Measurements of human lower leg were performed in a total acquisition time of TANa = 10:54 min/TAK = 8:06 min and using a nominal spatial resolution of 2.5 × 2.5 × 15 mm 3 /7.5 × 7.5 × 30 mm 3 for 23 Na/ 39 K MRI. Two aTSC and aTPC examinations in muscle tissue were performed during the same day on 10 healthy subjects. Results: The proposed acquisition and postprocessing workflow for 23 Na and 39 K MRI data sets provided reproducible aTSC and aTPC measurements. In human calf muscle tissue, the coefficient of variation between scan and re‐scan was 5.7% for both aTSC and aTPC determination. Overall, mean values of aTSC = (17 ± 1) mM and aTPC = (85 ± 5) mM were measured. Moreover, for 39 K in calf muscle tissue, T 2 ∗ components of T 2 f ∗ = (1.2 ± 0.2) ms and T 2 s ∗ = (7.9 ± 0.9) ms, as well as a residual quadrupolar interaction of ω q ¯ = (143 ± 17) Hz, were determined. The fraction of the fast component was f = (58 ± 4)%. Conclusion: Using the presented measurement and postprocessing approach, a reproducible aTSC and aTPC determination using 23 Na and 39 K MRI at 7 T in human skeletal muscle tissue is feasible in clinically acceptable acquisition durations.